1987
DOI: 10.1093/geronj/42.2.228
|View full text |Cite
|
Sign up to set email alerts
|

Life Satisfaction and Quality of Life Among Disabled Elderly Adults

Abstract: This paper investigates predictors of life satisfaction and quality of life among severely disabled elderly adults. Markides and Martin's (1979) path analysis model was adapted specifically to elderly persons with severe disabilities. The study group comprised 97 patients discharged from three medical rehabilitation facilities in metropolitan Boston during 1984. The adapted model explained about 40% of the variance in quality of life among both men and women, with functional capacity being the most important p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(34 citation statements)
references
References 0 publications
3
29
0
2
Order By: Relevance
“…This finding was similar to our previous study (7) among HD patients, a study (15) that reported a survey of Japanese elderly, and a study (32) of disabled elderly adults who were admitted for medical rehabilitation in the U.S. Therefore, spending the day actively may be associated with increased psychological well-being among HD patients as it is in elderly people dwelling in the community or in institutions.…”
Section: Discussionsupporting
confidence: 90%
“…This finding was similar to our previous study (7) among HD patients, a study (15) that reported a survey of Japanese elderly, and a study (32) of disabled elderly adults who were admitted for medical rehabilitation in the U.S. Therefore, spending the day actively may be associated with increased psychological well-being among HD patients as it is in elderly people dwelling in the community or in institutions.…”
Section: Discussionsupporting
confidence: 90%
“…The life domains of social well-being, physical well-being, psychological well-being, cognitive well-being, spiritual well-being, and environmental well-being as well as their indicators are common and consistently included to some extent in many of these existing measurement instruments. However, there are several limitations to the measurement of quality of life, including, (a) restricting measurement to one model (e.g., HRQoL) (Baker and Intagliata 1982;Baxter and Shetterly 1998;Bond 1999;Bury and Holme 1990;Cairl et al 1999, Capitman et al 1997Coons and Mace 1996;Farquhar 1994Farquhar , 1995Galambos 1997;Gamroth et al 1995;Livingston et al 1998;Marinelli and Plummer 1999;Noelker and Harel 2001;Osberg et al 1987;Raphael et al 1997), (b) limiting inquiries of quality of life ratings to a single source (e.g., perspective of a clinical provider) (Becker et al 1993Cairl et al 1999;Diaz and Mercier 1996;Diaz et al 1999;Kane 2001;Kane and Kane 2001;Rabiner et al 1997), and (c) evaluating quality of life among older people with disabilities/mental health issues such as dementia or Alzheimer's disease (Albert et al 1996(Albert et al , 1997Atchley 1991;Bond 1999;Raphael et al 1997). Baker and Intagliata (1982) identified additional problems with measuring quality of life that include insensitivity of quality of life measures, lack of data on normal fluctuations of mood states, limited norms of target populations, and the need for more consumer perspectives of quality of life.…”
Section: Quality Of Life Review: Limitations Of Measurementsmentioning
confidence: 99%
“…Similarly, studies of time use in persons with disability have revealed valuable information about the restricting aspects of particular handicapping factors. These include environmental constraints (physical, social, institutional, economic, cultural factors) (Law, 1993;Schalock & Genung, 1993); impaired social network (Astrom et al, 1992;Morgan & Jongbloed, 1990); and income (Osberg, McGinnis, DeJong, & Seward, 1987).…”
Section: Relationships Between Disability and Use Of Timementioning
confidence: 99%